2019
DOI: 10.1016/j.nbd.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and neuroprotection in stroke: Cationic arginine-rich peptides (CARPs) as a novel class of mitochondria-targeted neuroprotective therapeutics

Abstract: Stroke is the second leading cause of death globally and represents a major cause of devastating long-term disability. Despite sustained efforts to develop clinically effective neuroprotective therapies, presently there is no clinically available neuroprotective agent for stroke. As a central mediator of neurodamaging events in stroke, mitochondria are recognised as a critical neuroprotective target, and as such, provide a focus for developing mitochondrial-targeted therapeutics. In recent years, cationic argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 290 publications
(270 reference statements)
0
25
0
Order By: Relevance
“…A variety of mitochondrial targeting peptides can be used in the treatment of diseases [ 22 , 23 ]. The new beneficial effect of MitoQ on renal tubular injury in diabetic kidney disease was demonstrated by in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of mitochondrial targeting peptides can be used in the treatment of diseases [ 22 , 23 ]. The new beneficial effect of MitoQ on renal tubular injury in diabetic kidney disease was demonstrated by in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CARPs have emerged as a novel class of potential neuroprotective therapeutics for a broad range of acute brain injuries and chronic neurodegenerative disorders. These CARPs include short-chained polyarginine peptides [11,13,27], SS-peptides [28,29], APOE-derived peptides [27,30], and TAT-fused peptides, including TAT-NR2B9c (NA-1) and JNK1-TAT [11,31]. Such CARPs have been shown to exert their neuroprotective action through a variety of targets, which include structural and functional preservation of mitochondria [32], reduced ROS generation [33], inhibition of protein aggregation [34], modulation of glutamate or calcium ion receptors (excitotoxicity/calcium influx) [35], and activation of pro-survival signaling [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis also revealed that R18 preserved protein expression profiles pertaining to mitochondrial bioenergetics and structural integrity. Mitochondria are central mediators of intracellular calcium signaling events during excitotoxicity, and as such, are considered the "judge, jury, and executioner" of the cell [31,43].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is considered a vital component of the development of cerebral I/R injury [30]. Excessive mitochondrial fission promotes mitochondrial outer membrane permeability and increases Cyto c release, subsequently activating the apoptotic cascade reaction and eventually aggravating neurological damage [13,31]. Moreover, in a study by Wang et al [32], adenoviral Fis1, which can induce Fis1 overexpression, increased mitochondrial fission and apoptosis, whereas Fis1 knockdown attenuated mitochondrial fission and apoptosis.…”
Section: Discussionmentioning
confidence: 99%